2012
DOI: 10.1186/1742-2094-9-143
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 as a novel treatment for persistent hyperalgesia

Abstract: BackgroundChronic pain is often associated with microglia activation in the spinal cord. We recently showed that microglial levels of the kinase G protein–coupled receptor kinase (GRK)2 are reduced in models of chronic pain. We also found that mice with a cell-specific reduction of around 50% in GRK2 level in microglia/macrophages (LysM-GRK2+/− mice) develop prolonged inflammatory hyperalgesia concomitantly with ongoing spinal microglia/macrophage activation. The microRNA miR-124 is thought to keep microglia/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 32 publications
2
124
1
Order By: Relevance
“…Recently, it was demonstrated that a sufficient miR-124 concentration is crucial for its effectiveness [42]. Earlier experiments using either repetitive injection of the miR-124 mimic every 2e3 days after disease onset [10] or intracranial miR-124 expression through viral vector injection [14] prolonged the protective effects over weeks.…”
Section: Consequences For Therapeutic Planningmentioning
confidence: 99%
“…Recently, it was demonstrated that a sufficient miR-124 concentration is crucial for its effectiveness [42]. Earlier experiments using either repetitive injection of the miR-124 mimic every 2e3 days after disease onset [10] or intracranial miR-124 expression through viral vector injection [14] prolonged the protective effects over weeks.…”
Section: Consequences For Therapeutic Planningmentioning
confidence: 99%
“…We identified nociceptor GPCR kinase 2 (GRK2) as a novel regulator of the duration of inflammatory hyperalgesia (21)(22)(23)(24)(25)(26)(27). GRK2 restrains signaling by promoting desensitization of GPCRs (28) and/or by interacting with multiple components of intracellular signaling pathways (22,29,30).…”
Section: Introductionmentioning
confidence: 99%
“…They have proposed that intrathecal miR-124 treatment might be a powerful novel treatment for pathological chronic pain with persistent microglia activation. A decreased level of microglia miR-124 observed in LysM-GRK2 +/-mice when hyperalgesia became chronic [84]. Administration of miR-124 prevented persistent pain the mice.…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 98%